Correlation between Oxidized Low Density Lipoproteins and von Willebrand Factor in Chronic Renal Failure - Holvoet, Paul; Donck, Jan; Landeloos, Michèle; Brouwers, Els; Luijtens, Kristel; Arnout, Jozef; Lesaffre, Emmanuel; Vanrenterghem, Yves; Collen, Désiré (Thrombosis and Haemostasis, 1996)
An ELISA specific for a wide spectrum of oxidized apo B-100 in OxLDL was developed and applied to blood samples from 27 control subjects, 20 mild chronic renal failure (MCRF) patients, 21 severe chronic renal failure patients on conservative treatment (SCRF) and 56 severe chronic renal failure patients on maintenance hemodialysis (HEMO). Mean levels of OxLDL were 0.59 mg/dl in controls (95% Cl, 0.52-0.66 mg/dl), and were 2.7-fold (p <0.01), 3.1-fold (p <0.001) and 5.4-fold (p <0.001) higher in MCRF, SCRF and HEMO patients, respectively. Levels of von Willebrand factor, a marker of endothelial injury, were 100 percent in controls (95% Cl, 90-110 percent), and were 1.5-fold (p = NS), 1.6-fold (p <0.01) and 2.1-fold (p <0.001) higher in MCRF, SCRF and HEMO patients, respectively. Multiple regression analysis revealed that the extent of renal failure (F = 14; p = 0.0004) accounted for a significant fraction of the variation in OxLDL levels, also after exclusion of patients with evidence of ischemic atherosclerotic disease (F = 21; p = 0.0001). After adjustment for the extent of renal failure, hemodialysis (F = 5.6; p = 0.021) and LDL cholesterol levels (F = 7.1, p = 0.0095) contributed significantly to the variation in OxLDL levels. Whereas the extent of renal failure contributed only marginally to the individual variations in vWF levels (F = 4.1; p = 0.048), these levels correlated significantly with plasma levels of OxLDL (F=26; p=0.0001). In conclusion, atherogenic OxLDL increase progressively during the development of renal failure suggesting that the oxidation of LDL may be associated with endothelial injury and atherogenesis in these patients.